Palliative nursing care for Coronavirus Infection 2019 - Artsanthia, Jintana; Srisa-art, Rata; Sumet , Sr.Terasa Somsree (Journal of Public Health Nursing, 2021)
Nurses can play an essential palliative care role for vulnerable populations during critical times such as have occurred with the Coronavirus Infection 2019. Older adults and those with chronic illness often need special palliative care as they face severe infection from Coronavirus, sometimes leading to death. Providing palliative care nursing is urgent in reaching patients and their families so advance care plans can be devised should sudden death occur from the disease. Symptoms of Covid-19 disease are often severe and change quickly, leading to death. Palliative care can help patients and families with end-of-life decisions. Coronavirus infection is a condition, often with rapid onset and death that calls for palliative care. As part of the nurse’s role in improving the quality of life of patients and families is the preparatory role of providing end-of-life and bereavement care at the death of a patient.